Pelatihan Komunikasi Asertif dengan Teknik Psychoeducational Intervention untuk Mencegah Cyberbullying - Karyanti, Karyanti; Syarif, Dina Fariza Tryani; Fatchurahman, M. (Borneo Research and Education Center, 2024)
The training held in the Stimulus Community Partnership Program Community Service (PKMS) is aimed at employees in the UMPR environment. Implementation of assertive communication training using psychoeducational intervention techniques to prevent cyberbullying at SMK Negeri 3 Palangka Raya as a solution to problems faced by students who are in the adolescent phase and tend to be involved in cyberbullying either as perpetrators or victims. Cases of cyberbullying in the school environment do not only involve students as bullies and victims. Incidents of cyberbullying are increasing internationally and are considered a problem both inside and outside of school. Cyberbullying has received attention because it affects many individuals of various ages in a variety of settings, especially adolescents. The training activities were implemented for one day on August 15, 2022. The training participants totaled 150 students. Based on the results of the analysis of the success of the training, 91% of students experienced increased knowledge about cyberbullying and had assertive communication skills.